In creating the image of Ibn Sina, the reality of life and artistic fabric (Multidisciplinary Journal of Science and Technology, 2025)
The creation of historical reality and the character of a historical person in fiction is a complex process, in which creators create styles specific to each event and event and refer to genres when creating a work of art. This can only be confirmed by the colorful aspects used in the creation of the image of Ibn Sina, the great scholar of the East.